2021
DOI: 10.1016/j.clim.2021.108726
|View full text |Cite
|
Sign up to set email alerts
|

Genetic justification of severe COVID-19 using a rigorous algorithm

Abstract: Recent studies suggest excessive complement activation in severe coronavirus disease-19 (COVID-19). The latter shares common characteristics with complement-mediated thrombotic microangiopathy (TMA). We hypothesized that genetic susceptibility would be evident in patients with severe COVID-19 (similar to TMA) and associated with disease severity. We analyzed genetic and clinical data from 97 patients hospitalized for COVID-19. Through targeted next-generation-sequencing we found an ADAMTS13 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 73 publications
(61 reference statements)
0
33
1
1
Order By: Relevance
“…In addition, it was reported that the median activity of the VWF cleaving protease ADAMTS-13 (a disintegrin and metalloproteinase with a thrombospondin type 1 motif, member 13) in COVID-19 patients was lower than the expected median of the normal reference range, and the VWF to ADAMTS-13 ratio was associated with COVID-19 disease severity [ 95 ]. Interestingly, genetic analysis demonstrated that a missense variant of ADAMTS-13 was associated with ICU hospitalization in COVID-19 [ 96 ]. These findings suggested that SARS-CoV-2 infection is associated with consumption and hyperactivation of platelets.…”
Section: Platelet Activation and The Coagulation Cascade In Covid-19mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, it was reported that the median activity of the VWF cleaving protease ADAMTS-13 (a disintegrin and metalloproteinase with a thrombospondin type 1 motif, member 13) in COVID-19 patients was lower than the expected median of the normal reference range, and the VWF to ADAMTS-13 ratio was associated with COVID-19 disease severity [ 95 ]. Interestingly, genetic analysis demonstrated that a missense variant of ADAMTS-13 was associated with ICU hospitalization in COVID-19 [ 96 ]. These findings suggested that SARS-CoV-2 infection is associated with consumption and hyperactivation of platelets.…”
Section: Platelet Activation and The Coagulation Cascade In Covid-19mentioning
confidence: 99%
“…Furthermore, C5a induces NET formation through activation of its receptor on neutrophils, which triggers thromboinflammation and endothelial injury in COVID-19 [ 136 ]. Interestingly, genetic variants of complement pathway genes, including C3, factor H, and complement decay-accelerating factor, were reported to be significantly associated with clinical outcomes in COVID-19 [ 96 , 137 ]. Collectively, SARS-CoV-2 infection might result in unrestrained complement activation for endothelial cell dysfunction and thrombosis.…”
Section: Endothelial Dysfunction In Covid-19mentioning
confidence: 99%
“…Our finding revealed, like in the lung tissues infected with SARS-CoV-2 [ 52 ], decreased deposition of the regulatory complement component FH in the kidney tissues of COVID-19 patients, which may have enabled uncontrolled complement activation and deposition. Recently, variants of the FH gene were reported to be associated with severe clinical outcome in COVID-19 patients [ 53 ]. This implies that certain individuals have limited ability to control complement activation and accordingly they are more susceptible to severe disease.…”
Section: Resultsmentioning
confidence: 99%
“…They reported multiple other associations such as chromosome 12q24.13 (encodes antiviral restriction enzyme activators), chromosome 19p13.2 (encodes tyrosine kinase 2), chromosome 19p13.3 (encodes dipeptidyl peptidase 9) and chromosome 21q22.1 (encodes interferon receptor IFNAR2). Gavriilaki et al reported ADAMTS13 variants which were associated with ICU hospitalizations [ 27 ]. These findings may also explain variability of association between blood group types in different studies from different regions in the world.…”
Section: Discussionmentioning
confidence: 99%